Need of Integrating Sonoscopy in Undergraduate Medical Education in Developing Countries - Thapa, Amit (Journal of Nepal Health Research Council, 2020)
Early exposure to technical knowledge improves dexterity and encourages ingenuity. We see the role of ultrasound as a “sonoscope”. Use of sonoscope improves anatomical understanding and improves virtual image interpretation (mind’s eye). Early sonoscope use does not interfere with learning physical examination rather it improves one’s sensitivity as one sees what lies underneath one’s hand. Sonoscope is being used by various medical specialities not only to make diagnosis, but also to monitor and guide interventions. Medical schools worldwide have realised the need and relevance of sonoscope in medical curriculum and hence this needs to be integrated in undergraduate medical education in developing countries. Keywords: Medical education; point of care ultrasound (POCUS); sonoscope